2017
DOI: 10.1371/journal.pone.0174465
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the NK cell pool in HIV/HCV co-infection

Abstract: BackgroundA relevant proportion of human immunodeficiency virus (HIV) infected patients is co-infected with the hepatitis C virus (HCV). HCV co-infection in HIV-positive patients is associated with faster progression of liver disease in comparison to HCV mono-infection. Natural killer (NK) cells critically modulate the natural course of HCV infection. Both HIV and HCV mono-infection are associated with alterations of the NK cell pool. However, little data is available concerning phenotype and function of NK ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 66 publications
2
16
0
Order By: Relevance
“…It is evident that experimental settings, for example, cytokine prestimulation of NK cells, evaluation of spontaneous degranulation, and interaction with other immune cells are critical when analysing ex vivo NK cell cytotoxicity. Together, our results are consistent with those reporting impaired functionality of NK cells during HCV monoinfection , and also HIV/HCV coinfection . However, they could be also interpreted in the context of a functional NK cell dichotomy, where NK cells display a decreased production of antiviral cytokines but an enhanced basal cytotoxicity, which is impaired when these cells are exposed to their targets .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It is evident that experimental settings, for example, cytokine prestimulation of NK cells, evaluation of spontaneous degranulation, and interaction with other immune cells are critical when analysing ex vivo NK cell cytotoxicity. Together, our results are consistent with those reporting impaired functionality of NK cells during HCV monoinfection , and also HIV/HCV coinfection . However, they could be also interpreted in the context of a functional NK cell dichotomy, where NK cells display a decreased production of antiviral cytokines but an enhanced basal cytotoxicity, which is impaired when these cells are exposed to their targets .…”
Section: Discussionsupporting
confidence: 92%
“…Association between NK cell phenotype and function and the outcome of acute HCV infection was extensively reported , nevertheless, it remains unclear whether phenotypical and/or functional characteristics of NK cells are actually determinants for the rate of liver fibrosis progression. We and others have previously shown an association between low NK and CD4 + T‐cell counts with advanced liver fibrosis in HIV/HCV‐coinfected individuals . Here, we provide further support for this phenomenon, and also demonstrate that NK functionality is significantly impaired in coinfected individuals with advanced fibrosis.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The inhibition of degranulation observed in the functional assays was an unexpected result, as several studies report higher cytotoxic capacity in blood‐derived NK cells of HCV patients, mainly due to TRAIL upregulation. However, recent studies have reported a downregulation of CD107a and inhibition of degranulation of NK cells isolated from the blood of HCV and HCV/HIV coinfected patients after coincubation with HCV‐infected hepatocytes . Furthermore, Fugier and colleagues have shown that, in vivo, NK cell degranulation activity can be significantly impaired in patients with highest inflammation and fibrosis Metavir scores .…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous drug users may be at risk of both infections, and intravenous drug users represent the most common cause of new HCV infections [1]. Co-infection with HCV and HIV also appears to alter the host immune system, with strong evidence of decreased natural killer cells [45]. Clinicians also must exercise caution as there remains a possibility of drug-drug interaction, including hepatotoxicity between Highly Active-Antiretroviral Therapy (HAART) and DAA Direct-Acting Antivirals in Chronic Hepatitis C Infection with Liver Cirrhosis DOI: http://dx.doi.org/10.5772/intechopen.83609 [2].…”
Section: Direct-acting Antivirals In Hcv/hiv Co-infected Patients Andmentioning
confidence: 99%